Integrated meta‐QTL and in silico transcriptome assessment pinpoint major genomic regions responsible for spike length in wheat (Triticum aestivum L.) - Changgang Yang; Xueting Zhang; Shihong Wang; Na Liu (The Plant Genome)
Abstract Spike length (SL) is one of the major contributors to wheat yield. Uncovering major genetic regions affecting SL is an integral part of elucidating the genetic basis of wheat yield traits and goes further pivotal for marker‐assisted selection breeding. A genome‐wide meta‐quantitative trait locus (MQTL) analysis of wheat SL resulted in the refinement of 48 MQTLs using 227 initial QTLs retrieved from previous studies published over the past decades. The average confidence interval (CI) of these MQTLs amounted to a 5.16‐fold reduction compared to the mean CI of the initial QTLs. As many as 2240 putative candidate genes (CGs) were identified from the MQTL intervals using transcriptomics data in silico of wheat, of which 58 CGs were identified based on wheat–rice homology analysis. For the key CG affecting SL, a functional kompetitive allele‐specific PCR (KASP) marker, TaPP2C‐3B‐KASP, was developed to distinguish TaPP2C‐3B‐Hap I and TaPP2C‐3B‐Hap II based on the single nucleotide polymorphism at the 272 bp (A/G). The frequency of the elite allelic variation TaPP2C‐3B‐Hap II with high SL remained relatively stable at about 49.62% from the 1960s to 1990s. Integration of MQTL analysis and in silico transcriptome data led to a significant increase in the reliability of CGs for the genetic regulation of wheat SL, and the haplotype analysis for key CGs TaPP2C‐3B of SL provided insights into the biological function of the TaPP2C‐3B gene.